Factors Contributing to Unwanted Birth in India: Evidence from Panel Study Design - Anjali Bansal; Laxmi Kant Dwivedi; Priyanka Dixit; Amrita Gupta (Online Journal of Health & Allied Sciences)
Approximately 1 in 16 women worldwide face an unwanted pregnancy each year. According to the latest round of NFHS-5 (2019-22), in India, eight per cent of women reported unwanted birth during the last five years and exhibited a nine percent unmet need for contraception. The paper attempted to examine the association of different predictor variables on the unwanted bearing using the IHDS panel data conducted in 2004-05 and 2011-12. The bivariate and multivariable logistic regression model was employed to examine the determinants of unwanted births among Indian women. The results show that out of the total women who wanted to cease childbearing in 2004-05, 26% experienced unwanted births in between the surveys. The multivariable logistic model showed that Muslim women were more likely to report unwanted childbearing than Hindu women (AOR-2.81, 95% CI (1.73,4.59)). Contraception use also determined the unwanted bearing among the women, and contraceptive users were 80% less likely to report unwanted pregnancy (AOR-0.21 95% CI (0.18, 0.24)) than non-users. Husbands’ involvement can never be neglected in infertility decisions, especially in India. When husbands desire additional children, women are more likely to experience unwanted births (AOR-5.80, 95% CI (4.72,7.11). The multivariate analysis also found that the odds of reporting unwanted pregnancy were low among those with at least one son (AOR- 0.52, 95% CI (0.43, 0.63)). There is a need to educate couples about the importance of small family size and reform the existing girl-child policies. In addition to women, husbands should also be counselled about the benefits of contraception use and the importance of a girl child.